PENGARUH KOMITMEN, MOTIVASI, DAN ROLE STRESS TERHADAP KEPUASAN KERJA AKUNTAN PUBLIK - Handayani, Dwi (Widya Warta, 2012)
The purpose of this research is to analyze the influence of commitment, motivation, and role stress toward job satisfaction of public accountants. The samples of this research were 52 public accountants that worked at registered public accountants office in East Java. The data were analyzed by the use of SPSS program. The result of the analysis showed that professional and organizational commitments influenced motivation; organizational commitment influenced role conflict; organizational commitment did not influence role ambiguity; professional commitment did not influence job satisfaction; organizational commitment did not influence job satisfaction; motivation did not influence job satisfaction;, role conflict did not influence job satisfaction, and role ambiguity did not influence job satisfaction. Motivation, role conflict, and role ambiguity were not variables intervening between organizational and professional commitments toward job satisfaction.